Origin of solid bitumen in the Maokou formation of Huayingshan in eastern Sichuan: insights from biomarkers and carbon isotopes of group compositions - Liu, Hao; Shi, Zejin; Tian, Yaming; Tan, Qian; Li, Wenjie; Wang, Yong; Luo, Wei; Ning, Keke; Tang, Shaoyu (Carbonates and evaporites, 2025)
Identifying the source of solid bitumen is a crucial step in oil and gas source correlation. The origin of solid bitumen in the Maokou Formation of the Huayingshan area has always been a subject of debate. This research explores the origin of solid bitumen in the Maokou Formation of Huayingshan through biomarker and carbon isotope analysis of 5 solid bitumen samples and 1 source rock sample. The results show that the solid bitumen originates from a strongly reducing, low-salinity marine environment, with predominant input from bacteria and algae, showing high-overmature stage of maturation. The tricyclic terpane distribution shows C 23 tricyclic terpane exceeds C 21 , and hopanes are dominated by C 30 H. Regular steranes exhibit an inverted “L” distribution with C 28 < C 27 < C 29 . An inversion of carbon isotope type-curves, characterized by δ 13 C aro < δ 13 C sat < δ 13 C nos < δ 13 C asp in marl and dolomite limestones, whereas in dolomites, it is δ 13 C asp < δ 13 C nos < δ 13 C sat < δ 13 C aro . The hydrocarbon source correlation suggests a strong genetic affinity between solid bitumen in the Maokou Formation reservoirs and source rocks from Maokou Formation I and Longmaxi Formation. Carbon isotope of group compositions type-curves suggest that solid bitumen in the dolomite limestones received more input from the Maokou Formation I, while solid bitumen in dolomite was more influenced by contributions from the Longmaxi Formation. A comprehensive analysis concludes that the inversion is a result of the segmented supply of hydrocarbons from source rocks under pervasive TSR and biodegradation.